Vitamin D supplementation in later life: a systematic review of efficacy and safety in movement disorders - Homann, Carl N.; Homann, Barbara; Ivanic, Gerd; Urbanic-Purkart, Tadea (Frontiers in Aging Neuroscience, 2024)
Introduction Nutrition plays a pivotal role in the multidisciplinary approach to rehabilitating middle to old-aged patients with neurological diseases including movement disorders (MDs). Despite the prevalence of vitamin D deficiency in many patients with MDs, data supporting supplementation’s effectiveness and safety is sparse and conflicting, therefore, our explicit objective was to provide an all-encompassing review of the subject. Methods A comprehensive search of PubMed, Embase, and other scientific databases was conducted up to November 1 2023. The searches included RCTs in all languages with human participants aged 35 and above and not meeting these requirements led to exclusion. Results Four studies on Parkinson’s disease (PD) and one on restless legs syndrome (RLS) including 369 MD patients, however, none in a rehabilitation context, were found. Although three of the four PD studies showed better outcomes, such as decreasing levodopa-induced dyskinesia or enhancing physical performance in some or all domains, the RLS study did not identify symptom improvement. The one serious adverse effect observed, cerebral infarction, aroused safety concerns, however its relationship to vitamin D consumption is questionable. Structurally the studies can be characterized by large variations in patient populations, in primary outcomes, and disease severity, but typically a relatively short duration of therapy in most cases. With other limitations such as the small number of studies, major trial design heterogeneity, limited sample sizes, and a greatly variable Cochrane risk of bias (RoB) evaluation, only a qualitative synthesis was feasible. Discussion Two main implications can be inferred from these results, which we interpret as cautiously promising but overall insufficient for firm recommendations. First, there is an urgent need for more research on the role of vitamin D in MDs in the middle- to older-aged population, particularly during rehabilitation. Second, given the benefits of vitamin D supplementation for those who are deficient, we recommend routine screening and supplementation for MD patients.